2023
DOI: 10.1084/jem.20220729
|View full text |Cite|
|
Sign up to set email alerts
|

PD-1 blockade and CDK4/6 inhibition augment nonoverlapping features of T cell activation in cancer

Abstract: We performed single-cell RNA-sequencing and T cell receptor clonotype tracking of breast and ovarian cancer patients treated with the CDK4/6 inhibitor ribociclib and PD-1 blockade. We highlight evidence of two orthogonal treatment-associated phenomena: expansion of T cell effector populations and promotion of T cell memory formation. Augmentation of the antitumor memory pool by ribociclib boosts the efficacy of subsequent PD-1 blockade in mouse models of melanoma and breast cancer, pointing toward sequential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Endogenous T-cell priming could be detected in our study, as pre-existing T-cell clones showed PD-1 blockade-induced expansion in the blood. This phenomenon was much more restrained than in similar analyses of paired peripheral blood samples in patients with metastatic breast cancer ( 10 ) or resectable HNSCC ( 18 ) treated with PD-1 blockade, although tumor sequencing was more extensive in the latter study, making it difficult to conclusively ascribe the observed differences to a defect in priming as opposed to better cross-matching of circulating T cells to their tumor-infiltrating counterparts. Collectively, these findings suggest that T-cell priming in PDAC does occur at a level consistent with other tumor types.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Endogenous T-cell priming could be detected in our study, as pre-existing T-cell clones showed PD-1 blockade-induced expansion in the blood. This phenomenon was much more restrained than in similar analyses of paired peripheral blood samples in patients with metastatic breast cancer ( 10 ) or resectable HNSCC ( 18 ) treated with PD-1 blockade, although tumor sequencing was more extensive in the latter study, making it difficult to conclusively ascribe the observed differences to a defect in priming as opposed to better cross-matching of circulating T cells to their tumor-infiltrating counterparts. Collectively, these findings suggest that T-cell priming in PDAC does occur at a level consistent with other tumor types.…”
Section: Discussionmentioning
confidence: 89%
“…Single-cell RNA sequencing (scRNA-seq) was performed as previously described ( 10 ). Briefly, sorted single-cell suspensions prepared from each sample were washed twice with 0.05% UltraPure BSA (Invitrogen #AM2618) in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a very promising treatment for advanced breast tumors (hormone receptor-positive) with the drug CDK4/6, a cyclin-dependent kinase inhibitor that restores the immune response ( 58 , 59 ). Blocking PD-1 concomitantly with the administration of CDK4/6 has a synergistic protective effect against tumors by restoring T effector populations and promoting the formation of central memory T cells that preserve the immune-activating effect of α-CPI treatment ( 57 ). Studying the joint blockade of checkpoint molecules and drugs that stimulate central memory T cells in pulmonary PCM would be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CD4 + T/CD8 + T was independent factor for disease-free survival of stage I–IIIA lung cancer ( 22 ). PD-1 and PD-L1 inhibitors block the binding of PD-L1 on the surface of tumor cells and PD-1 on the surface of activated lymphocytes, and enhance the killing effect of immune cells on tumor cells ( 23 , 24 ). However, not all patients with advanced NSCLC benefit from immunotherapy.…”
Section: Introductionmentioning
confidence: 99%